Pengaruh Penggunaan Topologi Mesh terhadap Perkembangan Jaringan Wireless di Era Sekarang - Muhamad Eko Maulana; Nabihi Ramdhani; Mahmudin Mahmudin (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2025)
In the digital era, the internet has become a primary necessity for people in both urban and rural areas, driving the development of wireless networks such as Wireless Mesh Networks (WMN) that connect nodes in a multi-hop, self-organizing manner. WMNs offer advantages including flexibility, resilience, automatic configuration, self-healing capabilities, and cost efficiency, making them suitable for various sectors, including industry, residential areas, offices, and education. This research employs a qualitative approach through literature review on wireless networks and Mesh topology. Descriptive analysis is conducted to evaluate the strengths, weaknesses, and operational mechanisms of Mesh topology. The findings indicate that implementing Mesh topology in wireless networks provides reliable, flexible, and fault-tolerant connectivity, as each node can function as both a router and a data transmitter/receiver. Although installation is complex and requires numerous cables or ports, Mesh topology remains an effective solution to the limitations of conventional wired and wireless networks. Its advantages in redundancy, security, and scalability make Mesh topology a viable primary choice for the development of modern networks.